Spherical Ruthenium Disulfide-Sulfur-Doped Graphene Composite as an Efficient Hydrogen Evolution Electrocatalyst - Yu, J.; Guo, Y.; Miao, S.; Ni, M.; Zhou, W.; Shao, Zongping (American Chemical Society, 2018)
© 2018 American Chemical Society. The exploition of cost-efficient and high-performance catalysts to boost hydrogen generation in overall water splitting is crucial to economically obtain green hydrogen energy. Herein, we propose a novel electrocatalyst consisting of spherical RuS2 on S-doped reduced graphene oxide (s-RuS2/S-rGO) with high catalytic behavior toward hydrogen evolution reaction (HER) in all pH conditions, especially in alkaline electrolytes. RuS2/S-rGO delivers small overpotentials of 25 and 56 mV at current densities of 10 and 50 mA cm-2, respectively, and a low Tafel slope of 29 mV dec-1 with good stability for 100 h in basic solutions. This performance is comparable to and even exceeds that of documented representative electrocatalysts, including the benchmark Pt/C; since the price of Ru is about 1/25th that of Pt, this novel electrocatalyst offers a low-cost alternative to Pt-based HER electrocatalysts. Ruthenium-centered sites of RuS2 in this hybrid catalyst are responsible for the HER active sites, and S doping in RuS2 also exerts an important function for the HER activity; density functional theory calculations disclose that the water dissociation ability and adsorption free energy of hydrogen intermediate adsorption (?GH*) for RuS2 are very close to those of Pt. A homemade electrolyzer with an s-RuS2/S-rGO (cathode)//RuO2/C (anode) couple presents a relatively low voltage of 1.54 V at a current density of 20 mA cm-2, while maintaining negligible deactivation over a 24 h operation.